Pilot-scale calcination of limestone in steam-rich gas for direct air capture - Erans, María; Nabavi, Seyed Ali; Manovic, Vasilije (Elsevier, 2019)
A novel polygeneration concept, which has been proposed recently, comprises a fuel-cell calciner integrated system in order to produce electricity and lime which can be used for direct air capture (DAC) to remove CO2 from the atmosphere. However, the scalability of the integrated system needs to be further studied. In this work, calcination of limestone under steam-rich conditions simulating flue gas from a solid oxide fuel cell (SOFC), and subsequent ambient carbonation has been explored. Limestone was calcined under two steam concentration (21% and 35% vol) conditions in a 25 kWth pilot-scale bubbling fluidised bed (BFB), and then exposed to ambient air to evaluate DAC performance. Samples were characterised in order to quantify the hydration and carbonation conversions over time and, therefore, their DAC capacity. It was observed that steam reduces calcination time, confirming its catalytic effect, while the calcination temperature remained the same regardless of the steam composition at the same CO2 partial pressure. Moreover, increasing steam concentration during calcination affected the material performance and DAC capacity at ambient conditions positively. Therefore, these findings demonstrate that limestone calcined under typical SOFC afterburner exhaust conditions is suitable as a DAC sorbent.
Keywords: calcination; steam; CO2 capture; direct air capture; limestone